2000
DOI: 10.1002/hep.510310231
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hepatitis B virus surface antigen-specific Th1 helper cell frequency of chronic HBV carriers is associated with a failure to produce antigen-specific antibodies in the Trimera mouse

Abstract: In chronic hepatitis B virus (HBV) infectionInfection with the hepatitis B virus (HBV) is one of the most common infectious diseases with an estimated 300 million chronic HBV carriers worldwide. 1 The high risk of patients with chronic hepatitis B (CHB) developing liver cirrhosis and hepatocellular carcinoma is associated with a high morbidity and mortality. Because HBV is a noncytopathic virus, liver injury is mainly mediated by the host immune response against virus-infected liver cells. 2 Strong HBV core/pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 51 publications
(57 reference statements)
0
27
0
Order By: Relevance
“…Until now, considerable evidence has suggested that the immune response is the key factor in the pathogenesis of CHB [1][2][3][4]. Numerous studies have investigated the adaptive immune response with CD4 ϩ or CD8 ϩ T cells, B cells, or dendritic cells and the innate immune response with NK cells, in HBV-transgenic mice or in the monkey infection model; the results demonstrated that strong antiviral immune responses during the early stages of HBV infection could induce sustained viral clearance, whereas deficient immune responses could sustain infection [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, considerable evidence has suggested that the immune response is the key factor in the pathogenesis of CHB [1][2][3][4]. Numerous studies have investigated the adaptive immune response with CD4 ϩ or CD8 ϩ T cells, B cells, or dendritic cells and the innate immune response with NK cells, in HBV-transgenic mice or in the monkey infection model; the results demonstrated that strong antiviral immune responses during the early stages of HBV infection could induce sustained viral clearance, whereas deficient immune responses could sustain infection [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Every year, ϳ1 million people who are chronically infected with HBV die of liver failure, liver cirrhosis, or hepatocellular carcinoma [1,2]. It is known that HBV is not directly cytopathic for infected hepatocytes, and the clinical outcome of HBV infection or the degree of liver damage is the result of complicated interactions between the virus and the host immune response [3,4]. Some findings of studies of the immunopathogenesis of chronic HBV infection have suggested that CD8 ϩ T cells, CD4 ϩ T cells, and NK cells, as well as cytokines in the liver, participate in the process of liver pathology [5][6][7][8].…”
mentioning
confidence: 99%
“…Some of these cytokines lead to activities against pathogens, activate effector cells involved in the cellular interactions that occur during inflammation, and are part of the acute and chronic stages of viral hepatitis (22,35). The antibody response in patients with HBV infection plays a critical role in viral clearance through the formation of complexes with viral particles and their removal from the circulation (6,8,29).…”
mentioning
confidence: 99%
“…Studies carried out with cultures of peripheral blood mononuclear cells from patients with acute HBV infection showed a Th1-like cytokine pattern with increased levels of production of IFN-␥ and TNF-␣ (2,6). This high level of cytokine production stimulates the immune response, allowing the cure of HBV disease (21).…”
mentioning
confidence: 99%
“…For HBV therapy, it has been used to study specific T-cell responses, vaccination strategies (Bocher et al, 2000;Bocher et al, 2001) and the therapeutic effect of monoclonal antibodies directed against HBV epitopes (Eren et al, 2000;Galun et al, 2002). In addition, concerning HCV, an inhibitor of the internal ribosomal entry site and an anti-HCV monoclonal antibody were demonstrated to act as HCV inhibitors (Ilan et al, 2002) using this model.…”
Section: Perspective Box 2 Limitations Of Available Models For Studimentioning
confidence: 99%